Angiosarcoma of the Right Atrium with Extension to SVC and IVC Presenting with Complete Heart Block and Significant Pericardial Effusion - Hossein Vakili; Isa Khaheshi; Mehdi Memaryan; Shooka Esmaeeli (Case Reports in Cardiology)
Primary cardiac neoplasms are particularly unusual. Angiosarcoma is the most frequently seen histological subtype and is described by its infiltrating and damaging nature. Inappropriately, primary cardiac angiosarcoma is often missed as a preliminary diagnosis because of its scarcity. We present a 29-year-old previously healthy man with complete heart block and pericardial effusion who was finally diagnosed with angiosarcoma of the right atrium with extension to SVC and IVC.